Post-pandemic living: housing design for possible new residence mode - Shi, Xiaohui (My University, 2021)
Globally, people have switched to distance working in circumstance of COVID-19 and spend up to 24 hours at home. In the field of residence architecture, there is the need for transformation to adapt to diseases, as well as a foreseeing trend of working from home even after pandemic. Yet problems exist both physically and mentally. The paper aims to define a healthy dwelling environment that supports the possible new residence mode. Conclusions are drawn regarding the changes and demands in aspects of functions and spaces after the pandemic. The thesis is structured by three research questions: 1. What will be the changes or demands regarding scale and function for post-pandemic dwellings? 2. What kind of floor plan layout meets the need for post-pandemic living? 3. How to accommodate the 24-hour daily routine life in a limited area and ensure psychological well-being? Literature and reference cases study contribute to the theory part of the research. It’s further examined by designing a housing project in Majorna (Gothenburg) which strives for a healthy domestic environment. Several housing quality factors are identified： a. An apartment should be at least 50 ㎡ and better larger than 60 ㎡ as a minimum area even for the smallest household. It should include at least two and better three or more rooms. b. A separable open kitchen with sufficient space is an ideal plan to meet different needs. It’s good to have a dirt zone with cleaning facility at the entrance. Having an independent working space will be a growing need. Having private outdoor space is crucial. Loggia and mix type will offer the better integration compared to projecting balcony. c. Open-plan offers many good qualities while causing problems. Appropriate division method can prevent acoustic interference and enable parallel activities. Zoning and circular movements are ways to keep a balance between openness and division. The thesis hopes to contribute as an inspiration for designing future housing considering the potential new living pattern we are heading towards to.
Keywords: Covid-19, post-pandemic, apartment housing, work from home, healthy home